Discrete emotions in infancy: perception without production? - Höhl, Stefanie; Striano, Tricia (Emotion review, 2010)
Camras and Shutter review evidence suggesting that infants? facial expressions do not represent discrete emotions and cannot easily be matched to the facial expressions of adults. This raises the important question of whether infants have a notion about the meanings of discrete emotions at all. The authors do not discuss whether infants are sensitive to discrete emotional expressions when perceiving others. In our commentary we discuss evidence for the perception of discrete emotional facial expressions in infancy.